Current status and factors influencing kinesiophobia in patients with meniscus injury: a cross-sectional study - Faqiang Tang; Pan Xu; Cai Jiang; Xiaohua Ke; Dunbing Huang; Yaling Dai; Zhonghua Lin; Shizhong Wang (Journal of Orthopaedic Surgery and Research)
Abstract Objectives This study aimed to examine the relationships between kinesiophobia and injury severity, balance ability, knee pain intensity, self-efficacy, and functional status in patients with meniscus injuries and to identify key predictors of kinesiophobia. Design A single-center, prospective cross-sectional study. Methods A cross-sectional study involving 123 patients diagnosed with meniscus injuries at Fujian Provincial Hospital was conducted. The knee range of motion test was used to determine limitations in knee joint mobility, whereas magnetic resonance imaging (MRI) was used to assess the severity of meniscus damage. Several validated scales were administered: the Tampa Scale of Kinesiophobia (TSK-17) to measure kinesiophobia, the visual analog scale (VAS) to assess pain intensity, the general self-efficacy scale (GSES) to evaluate self-efficacy, and the Lysholm knee score (LKS) to assess knee functional status. Additionally, balance ability was assessed using the Huber 360 Neuromuscular Control Training and Assessment System (DJO, USA). Spearman’s correlation analysis was applied to explore factors associated with kinesiophobia, whereas simple linear regression analysis was used to identify its predictors. Results Among the 123 participants included in the study, 60.16% were identified as experiencing kinesiophobia. Among these participants, 69.10% had grade III meniscus injuries, and 33.3% exhibited limited joint movement. The key clinical characteristics were as follows: the median VAS score was 4 (IQR 2–6), the GSES score was 22 (IQR 20–29), and the LKS score was 45 (IQR 38–55). Kinesiophobia was significantly correlated with injury severity, limited joint movement, pain intensity, self-efficacy, and other functional parameters (P < 0.05). However, no significant correlation was detected between kinesiophobia and limits of stability. Simple linear regression analysis (R²=0.917) revealed several significant predictors of kinesiophobia, including injury severity (β = 2.08), pain intensity (β = 0.882), Romberg quotient (RQ) (β = 3.239), and limited joint movement (β = 0.868). In contrast, self-efficacy (β =-0.455) was negatively associated with kinesiophobia. Furthermore, Grade III injuries and RQ were found to be associated with markedly higher levels of kinesiophobia. Conclusion Kinesiophobia is strongly associated with knee injury severity, limited joint movement, RQ, pain intensity, and self-efficacy, which are key predictors. Clinical interventions should focus on these factors to enhance rehabilitation outcomes.